Implementasi Kurikulum Tingkat Satuan Pendidikan dalam Meningkatkan Kualitas Pendidikan di Universitas - Singgih Prastawa; Trisna Rukhmana; Yosep Heristyo Endro Baruno; Khasanah Khasanah; Aat Ruchiat Nugraha; Melinda Yusri Rizki (Departement of Mathematics Education, 2024)
This research discusses the implementation of the Education Unit Level Curriculum (KTSP) as a strategy to improve the quality of education in the university environment. The research methods used include surveys, interviews, and data analysis to evaluate the impact of KTSP implementation on student engagement, soft skills development, and stakeholder responses. The research results show that the implementation of KTSP has succeeded in improving the quality of education with more active student involvement, development of soft skills, and positive responses from stakeholders. The practical implication of this research is the importance of designing a curriculum that is responsive, relevant, and effective in achieving better educational goals at universities.